2004
DOI: 10.1093/nar/gki088
|View full text |Cite
|
Sign up to set email alerts
|

VBASE2, an integrative V gene database

Abstract: The database VBASE2 provides germ-line sequences of human and mouse immunoglobulin variable (V) genes. It acts as an interconnecting platform between several existing self-contained data systems: VBASE2 integrates genome sequence data and links to the V genes in the Ensembl Genome Browser. For a single V gene sequence, all references to the EMBL nucleotide sequence database are provided, including references for V(D)J rearrangements. Furthermore, cross-references to the VBASE database, the IMGT database and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(129 citation statements)
references
References 8 publications
0
129
0
Order By: Relevance
“…Eleven putative novel alleles (Table 2) were identified by applying the regression-based approach and filtering (described above) to the Ig sequencing data from seven subjects listed in Table 1. These alleles were missing from the IMGT database, and were also not present in VBASE2 (22) or the UNSWIg human heavy chain repertoire (23). Excluded from Table 2 are six alleles that were sequencing artifacts (further discussed in SI Text), and which were eventually removed by the genotyping process described later.…”
Section: Automated Methods Detects Novel Ighv Alleles From Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven putative novel alleles (Table 2) were identified by applying the regression-based approach and filtering (described above) to the Ig sequencing data from seven subjects listed in Table 1. These alleles were missing from the IMGT database, and were also not present in VBASE2 (22) or the UNSWIg human heavy chain repertoire (23). Excluded from Table 2 are six alleles that were sequencing artifacts (further discussed in SI Text), and which were eventually removed by the genotyping process described later.…”
Section: Automated Methods Detects Novel Ighv Alleles From Experimentalmentioning
confidence: 99%
“…However, recent studies have discovered the presence of numerous V segments and alleles not reported in any published databases (6,(19)(20)(21), as well as a several novel D and J alleles (19). Some of these V alleles have been incorporated into the IMGT database or alternative databases of germline alleles [such as VBASE2 (22) or the UNSWIg human heavy chain repertoire (23)]. The completeness of the germline V(D)J database may greatly influence downstream analysis results, including clinically relevant decision processes (24), as unreported alleles can skew estimated segment distributions and because novel polymorphisms will appear as recurrent somatic mutations.…”
Section: Significancementioning
confidence: 99%
“…The D and J H gene segments were identified using FUZZNUC software to search for heptamerenonamer like motifs. The V gene segments were detected by a BLAST search of the BAC sequence in combination with a procedure developed for the automatic generation of the database VBASE2 [34], and with manual sequence analyses. The positions and exon boundaries of IgH C domains were determined …”
Section: Screening Of Bac Library and Annotation Of Igh Gene Locusmentioning
confidence: 99%
“…In case 1, sequence analysis was performed on RNA extracted from peripheral blood mononuclear cells. In order to determine the level of somatic mutation, patients' sequences were aligned to the germline sequences in the V-BASE 2 database (Retter et al, 2005). The IGHV mutation status was designated as unmutated if there were fewer than 2% mutations (>98% homology to germline sequences), or as mutated if there were 2% or more mutations (£98% homology to germline sequences) compared to the germ-line sequences (Fais et al, 1998).…”
Section: Sequence Analysis Of the Ighv Genesmentioning
confidence: 99%